Understanding the pneumococcus: transmission and evolution - Donkor, Eric S. (Frontiers in Cellular and Infection Microbiology, 2013)
Streptococcus pneumoniae is part of the normal bacterial flora of the narsopharynx, but is also associated with several invasive and non-invasive diseases. Recently, there has been a plethora of research information on the pneumococcus, however, there are few comprehensive review papers discussing the research information. This paper provides a review of the pneumococcus in two vital areas related to its biology including transmission and evolution. Transmission of the pneumococcus is a highly efficient process that usually occurs through respiratory droplets from asymptomatic carriers. Following acquisition, the pneumococcus may only establish in the nasopharynx of the new host, or further progress to sites such as the lungs and cause disease. Pneumococcus transmission risk factors, as well as factors involved in its translocation from the nasophyarnx to diseases sites are still not fully understood. Pneumococcal evolution is dominated by recombination. The recombinational events usually involve genetic exchange with streptococci of the mitis group and some pneumococci are thought to exhibit hyper-recombination.